PENGARUH PENAMBAHAN LENGKUAS MERAH (Alppinia purpurata) TERHADAP KUALITAS DENDENG SAYAT IKAN BANDENG (Chanos chanos) SELAMA PENYIMPANAN - Rahmah, Rahmah; Wijaya, Muhammad; Mustarin, Amirah (Universitas Negeri Makassar, 2017)
This study aimed to determine the effect of adding red galangal (Alppinia purpurata) to chemical, microbiological, and organoleptic qualities during storage.The type of this research is a quantitative research with experimental approaches and designed using completely randomized factorial design consist of two factors, namely factor A was the addition of galangal (control, 3%, 5%, and 7%) and factor B was the long of storage (0 day, 10 day, 20 day, 30 day) at room temperature. The number of treatmented was tested that as much as 16 treatments combinations. Each treatment combination was repetition at 3 times to obtain 48 units experiment The The parameters observed in this research were water content, fat content, microbial colony count (ALT), sensory test of aroma and appearance of hedonic, texture, and taste of jerky the fish milkfish. Data were analyzed by variance analysis techniques (ANOVA) and continued by duncan test. The best treatment was jerky of milkfish fish with the addition of galangal 7% during storage that was the highest addition of galangal treatment. As long as the storage of test parameters decreases with time of storage. The treatment of the addition of galangal 7% was the best of product because it could still maintain the physical properties of the appearance, texture, aroma and taste of jerky the fish milkfish until the storage of the 10 day